"The Framing of Gay Candidate for Human Right Commissioner in the Religious-Based Indonesian Online Portals" - Listiorini, Dina; Sarwono, Billy; Hidayana, M. Irwan (KnE Social Sciences, 2019)
The representation of homosexuality in Indonesian media tends to be discriminative and negative, with stigma, prejudice, and stereotypes. It occurs not only in the mainstream but also in the cyber media such as online news-portals. The discriminating views against homosexuals have even penetrated into the political sphere. In 2012, when Dede Oetomo, an activist of LGBTIQ (Lesbian, Gay, Bisexual, Transgender, Intersex, and Queer) proposed as a candidate for the National Commission on Human Rights (Komnas HAM) commissioner, various reactions arose from people as he was exposed by the media. The controversy of Dede Oetomo’s candidacy occurs and spread widely, especially amongst online media portals. The public resistance to Dede Oetomo is mostly due to his gay identity. This paper studies how Dede Oetomo’s candidacy as the Human Right Commissioner is portrayed in the Indonesian online portals, based on Robert Entman’s framing model. The results show the online media portals’ framing of homosexual issues is still influenced by the majority religion (Islam) and the local cultural norms. The portals also differ from one another concerning the way they depict the issue although showing similar resentment towards homosexuality. Keywords: framing, homosexuality issues, online news, Dede Oetomo